LOYALITAS PELANGGAN DI TINJAU DARI COSTUMER BOUNDING DAN CITRA MEREK PADA PT.SURYA INTI PUTRA PAHLAWAN PROBOLINGGO - Dedi Joko Hermawan; Junaidi Junaidi (Gapenas Publisher, 2022)
Research aims to find out the influence of variable brand image and customer bonding on consumer loyalty. The population used by PT. Surya Inti Putra Pahlawan as many as 30 respondents based on non probability sampling technology to determine the sample of respondents were then analyzed using multiple linear regression and hypothesis tests with the help of the SPSS 22 program. The results showed: (1) the brand had no significant effect on the consumer loyalty of PT Surya Inti Putra Pahlawan; (2) customer bonding based on the results of the analysis also has a significant effect shown from the customer bonding relationship built better by PT Surya Inti Putra Pahlawan to consumers so as to increase loyalty to all consumers in the business field